2016
DOI: 10.17140/pnnoj-3-118
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Care After the First Day From Birth: A Case Control Study in a Northeastern Italian Hospital

Abstract: Background: Recently the use of antibacterial agents to clean and dry the stump of the newborns' umbilical cord (UC) after birth has been abandoned by many neonatal units. Aim of this study was to compare the occurrence of adverse events (AEs), time to UC separation and caregivers' satisfaction among newborns treated with dry cord care versus 70% alcohol after one day from birth in an Italian Hospital. Methods: From June 2014 to September 2014, 100 infants were enrolled for the study. Soon after birth, all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
3
9
1
Order By: Relevance
“…The incidence of granuloma in our research is very similar to that found by researchers at 8.7% [56] and 11.7% [42]. Studies have yielded conflicting results, with lower results such as 1-2% [36,54]. No studies found have compared the presence of umbilical redness with the type of delivery or with covering the navel with the diaper.…”
Section: Umbilical Complications After Separationsupporting
confidence: 88%
See 1 more Smart Citation
“…The incidence of granuloma in our research is very similar to that found by researchers at 8.7% [56] and 11.7% [42]. Studies have yielded conflicting results, with lower results such as 1-2% [36,54]. No studies found have compared the presence of umbilical redness with the type of delivery or with covering the navel with the diaper.…”
Section: Umbilical Complications After Separationsupporting
confidence: 88%
“…The presence of mild umbilical redness does not coincide with the results obtained by other studies, with values of 0.8% [52] or 7% [36]. Other authors have obtained a figure of 70% [54]. Our data are closer to the result of 30.5% [55].…”
Section: Umbilical Cord Healing Complicationscontrasting
confidence: 75%
“…This finding confirms that procedures was easy, understood, accepted and safe method, when students first trained on simulation. This finding was supported with Gallina, et al, (2016), which carried out a study entitled "Care of premature after the first day from birth" in a Northeastern Italian Hospital, and found that, there were significant difference between simulation and clinical group in prematurity care. In the same line these results were supported with Qiaoya, et al, (2016), the study which entitled" Novel visual nasogastric preterm feeding: feasibility and efficiency study in a manikin" in China who reported that the simulation group was significantly more than clinical group in feeding of preterm infant and showed that simulation group was more efficient and safer than clinical group.…”
Section: Discussionsupporting
confidence: 55%
“…As for quasi experiments, three studies were considered of medium quality, while the remaining studies were of high methodological quality [25-27]. The most remarkable deficient aspects related to study selection were employing a convenient sampling approach and inadequate sample selection/randomization (the first 50 infants were assigned to the dry care group and the last 50 infants to alcohol 70% group) [25, 27]. Regarding the comparability of the assigned groups, no information was available about the comparability of infants regarding gestational ages in two studies [25, 26].…”
Section: Resultsmentioning
confidence: 99%
“…The most remarkable deficient aspects related to study selection were employing a convenient sampling approach and inadequate sample selection/randomization (the first 50 infants were assigned to the dry care group and the last 50 infants to alcohol 70% group) [25, 27]. Regarding the comparability of the assigned groups, no information was available about the comparability of infants regarding gestational ages in two studies [25, 26]. In four studies, the ascertainment of infants’ interventions and the reported adverse events was not directly performed by healthcare providers, but rather only by self-reported data by the mothers as obtained one month or six weeks after birth.…”
Section: Resultsmentioning
confidence: 99%